The Influence of Employee Professionalism on the Quality of Public Services in the Mattiro Deceng Village Office, Tiroang District, Pinrang District - Irmayani; Andi Uceng; Kamaruddin Sellang (MultiTech Publisher, 2024)
Finding out what factors affect employee work professionalism at the Mattiro Deceng sub-district office, Tiroang sub-district, and Pinang district, as well as the impact of that professionalism on the quality of public services are the objectives of this research. A quantitative descriptive technique is employed in this research methodology. The study's sample consisted of 97 individuals from the Mattiro Deceng sub-district. Incidental sampling is the sampling strategy employed. This study included questionnaires, interviews, observation, and literature review as data gathering methods. After that, the data was processed and examined using Likert scales and quantitative descriptive analytic methods supported by descriptive statistics and SPSS. The results of the research show that the work professionalism of employees at the Mattiro Deceng sub-district office is categorized as good.